Friction-Induced Wellness in Sasak Culinary Tourism: Narrative Gastronomy and Experiential Transformation - I Wayan Induyoga Aditama; Lukman Ahmadi; Pandu Sapto Desmantyo; Muhammad Syakib 'Asqalani Rifai (JURNAL ECONOMINA, 2026)
This study analyzes the transformation of sensory and physical friction in Sasak culinary tourism into wellness experiences through narrative gastronomy. A qualitative case study approach was employed in two culinary tourism destinations in Lombok, Indonesia, namely Sade Traditional Village and Bilebante Tourism Village. Data were collected through participant observation, in-depth interviews, and documentation, and analyzed using thematic analysis to identify patterns of experiential transformation. However, limited attention has been given to how sensory and physical friction in culinary tourism can be transformed into wellness experiences through culturally mediated interpretation, particularly in vernacular culinary contexts. This study addresses this gap by examining how discomfort becomes a resource for psychological and emotional transformation. The findings show that tourists initially experience sensory overload, physical discomfort, and culture shock triggered by smoke, heat, strong aromas, and manual cooking practices. Through narrative gastronomy delivered by local actors, these frictions are cognitively reframed into cultural meanings associated with resilience, patience, and communal values. This process facilitates a transition toward mindfulness and flow state, characterized by heightened attention, embodied engagement, and sensory awareness. The experience further generates catharsis, gratitude, and social connectedness through communal food consumption. This study proposes the Friction-Induced Wellness Model as its main contribution. This model is among the first to explain how wellness in culinary tourism emerges not from comfort-based experiences, but through a culturally mediated transformation process involving sensory friction, narrative interpretation, and embodied participation.